MANAJEMEN LIMBAH B3 MEDIS DI RUMAH SAKIT RUJUKAN COVID-19 DI YOGYAKARTA SELAMA PANDEMI - Rahmadina, Frisca; Nababan, Rohani Angelia; Pranowo, Deni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: The inadequate management of medical waste could have significant repercussions on the environment and public health. This study sought to assess the medical waste management procedures implemented in Yogyakarta's COVID-19 national referral hospitals during the pandemic. This study employed a descriptive research design with a qualitative approach. Data were gathered through interviews, observations, and the analysis of secondary sources. The findings were then juxtaposed with the regulations outlined in the Minister of Environment and Forestry's Regulation Number 56 of 2015 and the Guidelines for Waste Management in Referral Hospitals, Emergency Hospitals, and Health Centers Handling COVID-19 Patients. The research findings revealed that the referral hospitals had experienced a decline in medical waste sorting, storage, and transportation practices. Additionally, the incineration process employed an incinerator with the burner set at 1200°C, a procedure exclusively conducted by Hospital Y. The management of medical waste in these hospitals adhered to the relevant guidelines and regulations.Keywords: Medical Waste, Infectious Waste, Waste Management, COVID-19